2023
DOI: 10.1038/s41598-023-33185-0
|View full text |Cite
|
Sign up to set email alerts
|

Tunable sulphur doping on CuFe2O4 nanostructures for the selective elimination of organic dyes from water

Abstract: In this work, sulphur doped copper ferrites (S-CuFe2O4) photocatalysts were successfully synthesized for the first time using the facile hydrothermal method. The as-synthesized photocatalysts were characterized through XRD, Raman, TGA, FT-IR, UV–Vis-DRS, SEM, EDX and PL techniques. The results revealed that doping with sulphur has been found to be a suitable alternative that causes strain in the lattices as anions replace the oxygen from the CuFe2O4 nanostructures. Due to sulphur dopants, photocatalysts are ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 44 publications
(14 citation statements)
references
References 89 publications
(86 reference statements)
0
14
0
Order By: Relevance
“…The higher recorded PL emission represents the maximum charge recombination rate and low photocatalytic efficiency of the material. 59 Meanwhile the low-intensity PL emission defines the high charge separation and maximum photocatalytic activity of the material. The PL emission of g-C 3 N 4 indicated a peak which was centred at 512 nm, while in the case of rutile TiO 2 a peak originated at 841 nm having less intensity as compared to g-C 3 N 4 .…”
Section: Resultsmentioning
confidence: 99%
“…The higher recorded PL emission represents the maximum charge recombination rate and low photocatalytic efficiency of the material. 59 Meanwhile the low-intensity PL emission defines the high charge separation and maximum photocatalytic activity of the material. The PL emission of g-C 3 N 4 indicated a peak which was centred at 512 nm, while in the case of rutile TiO 2 a peak originated at 841 nm having less intensity as compared to g-C 3 N 4 .…”
Section: Resultsmentioning
confidence: 99%
“…, MB, CV), which is due to stable xanthene ring structures in RhB. 25,64 By noticing the higher performances of Ag–BiVO 4 , a mixture of two dye solutions (RhB with MB, 5 ppm each) were used to degrade simultaneously. The activities obtained for the mixture of two dyes are presented in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…During the photodegradation of RhB, a blue shift is observed that is due to the de-ethylation of RhB. 25,65,66 The comparison of the degradation of MB and RhB over Ag–BiVO 4 catalysts is illustrated in Fig. 7b.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Metal vanadates, including BiVO 4 , CrVO 4 , FeVO 4 and Zn 3 V 2 O 8 , have also been reported for photocatalytic water splitting reactions. 10–17 CeVO 4 is an efficient photocatalyst with a suitable bandgap of 2.8 eV, and it is a commercially available and cost-effective material. 18 Some drawbacks were found in these photocatalysts, including rapid recombination of charge carriers and insufficient charge transfer.…”
Section: Introductionmentioning
confidence: 99%